Design of a New Type of Communication Substatio - XU Le-nian; GAO Shuang; LI Wen-jing (Gong-kuang zidonghua, 2011)
In view of problem that there are many kinds of sensor bus network composed by intelligent sensors in low level networks of safety monitoring and control system of coal mine, the paper proposed a design scheme of communication substation which is compatible with many kinds of communication modes. On the one hand, the substation can collect data of intelligent sensors with many kinds of digital interface. On the other hand, it not only can communicate with monitoring computer by traditional bus mode, but also can communicate with monitoring computer by optical fiber or industrial Ethernet. The actual application showed that the substation has good compatibility and reliability.